Relationship between the inner intercanthal distance and the mesiodistal dimension of maxillary anterior teeth in a peruvian population with facial harmony. - Valerie Saldaña-Carranza; Marcos J. Carruitero (Universidad de Concepción., 2019)
Objective: To determine the relationship between the inner intercanthal distance and the mesiodistal dimension of the maxillary anterior teeth in a Peruvian population with facial harmony. Material and Methods: A cross-sectional study on a sample of 75 Peruvian subjects with facial harmony, with ages ranging between 18 and 30 years, was conducted. The inner intercanthal distance and the mesiodistal dimension of maxillary anterior teeth of each subject were measured with a digital vernier caliper. The relationship was evaluated by simple linear regression analysis. Results: A statistically significant direct relationship was found between the dimension of the inner intercanthal distance with the mesiodistal width of the lateral incisors (p=0.040, R2=5.65%), canines (p=0.032, R2=6.17%), and the total mesiodistal sum of the six anterior teeth (p=0.040, R2=5.63%), but not with the central incisors (p=0.273, R2=1.64%). Conclusion: The inner intercanthal distance showed a direct relationship with the total mesiodistal linear dimension of the maxillary anterior teeth, with the mesiodistal dimensions of the lateral incisors and canines in a Peruvian population with facial harmony.